HMSIW- and QMSIW-based antenna for wireless communication application. Issue 1 (25th January 2021) - Vala, Alpesh; Patel, Amit V.; Mahant, Keyur; Chaudhari, Jitendra; Mewada, Hiren K.
Abstract : Purpose: The purpose of this paper is to design and develop half-mode substrate-integrated waveguide (HMSIW)- and quarter-mode substrate-integrated waveguide (QMSIW)-based antennas for wireless communication application. The developed antennas offer advantages in terms of compactness, high gain and better isolation between the ports. Design/methodology/approach: Initially, the tri-band substrate-integrated waveguide-based antenna is designed using a slot on the ground plane. Then, the same structure has been bisected into two parts for the development of the HMSIW structure. Again the concept of the slot is used for the realization of a dual-band antenna. QMSIW-based structure is designed with further dividing HMSIW structure into two parts. Simulation has been carried out with the use of a high-frequency structure simulator (HFSS) software, which used a finite element-based solver for the full-wave analysis. Findings: The proposed HMSIW-based dual-band antenna resonates at two different frequencies, namely, 5.81 GHz with 4.5 dBi gain and at 6.19 GHz with 6.8 dBi gain. Isolation between two ports is 20 dB. The overall dimensions of the proposed model are 0.39 λ × 0.39 λ. Similarly, QMSIW-based antenna is resonated at 5.66 GHz of the frequency with the 3 dBi gain. Frequency tuning is also carried out with the change in the slot dimension to use the proposed antenna in various C (4–8 GHz) band applications. Originality/value: The proposed antennas can use C band wireless frequency application. The proposed structure provides better performance in terms of isolation between the ports, small size, high front-to-back ratio and higher gain. It is fabricated for the proof of concept with the RT Duroid 5880 substrate material having a 2.2 permittivity. Measured results show a similar kind of performance as a simulated one.